Embodying regenring: Analysing the Genre Furoshiki using English's theoretical framework. (1st June 2018) - Gröppel-Wegener, Alke
Really my contribution to this issue is an artefact – a regenring of Fiona English's Orientations of Genres framework as a Furoshiki, a Japanese wrapping cloth. But as I cannot share this with all of you beyond a photograph, the best way of describing it within the constraints of a (printed) journal is as this article, part origin story, part analysis… but really this is the story of how by applying the framework, I started to understand it much better (and how I now propose to change it)! The purpose of this article is to use English's Orientations of Genres framework to compare the Genre Furoshiki (a Japanese wrapping cloth designed to represent said framework and to serve as a delegate pack for a workshop on using genre in higher education) to the two genres it grew out of – a summary of the framework itself, namely English's 2015 chapter 'Using genre as a pedagogical resource' (which we included in the material disseminated to delegates after the workshop), and the traditional conference tote bag so often used as a receptacle for a delegate pack. As the framework was developed with mainly linguistic genres in mind, it will be critiqued as to its suitability in discussing artefactual genres, and I argue that Gestalt Principles and Jacques Bertin's visual attributes make a useful extension to the framework itself.